2017
DOI: 10.24818/jamis.2017.030013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of board oversight functions on the performance of listed companies in Nigeria

Abstract: Abstract:We ascertain the impact of board oversight functions on the financial performance of listed companies. The study covers the entire 186 companies listed on the Nigeria stock exchange for a period of five years between 2010 and 2014. Three aspect of board oversight function which includes the audit committee function, risk management committee function and remuneration/human capital committee function were considered in this study in line with the provision of (SEC) code of corporate governance and (OEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(33 reference statements)
3
3
0
Order By: Relevance
“…For example, Hassink et al (2010) conducted a survey of a group of legal practitioner and forensic accountants and discovered that approximately 69% of the respondents testified to several cases of fraud being detected. Their strong agreement is also consistent with the findings of Ijeweremo (2015) and Oyerogba et al (2017) that reported a significant increase in the degree of effectiveness of forensic auditors in unveiling fraudulent practices in different sectors of the economy surveyed.…”
Section: Resultssupporting
confidence: 90%
“…For example, Hassink et al (2010) conducted a survey of a group of legal practitioner and forensic accountants and discovered that approximately 69% of the respondents testified to several cases of fraud being detected. Their strong agreement is also consistent with the findings of Ijeweremo (2015) and Oyerogba et al (2017) that reported a significant increase in the degree of effectiveness of forensic auditors in unveiling fraudulent practices in different sectors of the economy surveyed.…”
Section: Resultssupporting
confidence: 90%
“…As exposed by the outcome, it was observed that board size had a negative (-0.5222163) and p-value of insignificant (0.148) effect on the listed firms' profitability in Kenya. The outcome is consistent with Eyenubo (2013), however, the outcome is at variance with Tanna, Pasiouras, & Nnadi (2013); Oyerogba, Memba, and Riro (2016) and Tulung et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…The outcome is at variance with Tanna, Pasiouras, & Nnadi (2013) who concluded that the size of the governing body has a large influence on how profitable as well as effective an enterprise is. Oyerogba, Memba, and Riro (2016) demonstrated that the profitability of the traded firms is substantially influenced by the size of the board. Tulung et al (2018) showed that the size of the board as well as independence have a beneficial impact on the performance of a banking institution.…”
Section: Board Size and Profitability Of Manufacturing And Allied Fir...mentioning
confidence: 99%
“…The specific duties and responsibilities of the governance committee have been described to some extent in Hall et al (2005) and Leblanc et al (2012). Oyerogba et al (2017) developed a board oversight function index including 14 items related to the remuneration/governance committee function. Further business ethics descriptive studies depict the governance committee as a channel for receiving employee complaints (Lipman, 2007), a reporting authority referenced in the code of ethics of listed companies (Bodolica and Spraggon, 2015) and a board subcommittee that can help the audit committee strengthen business ethics (Marx and Els, 2009).…”
Section: Prior Academic Literature On Governance Committeesmentioning
confidence: 99%
“…The impact of governance committees seems non-significant on earnings management (Talbi et al , 2015), earnings per share and return on capital (Oyerogba et al , 2017) and corporate social responsibility reporting (Barakat et al , 2015; Dilling, 2009). However, the presence of a governance committee reduces aggressive financial reporting (Huang et al , 2009) and is associated with a higher level of voluntary disclosure (Ntim et al , 2017).…”
Section: Prior Academic Literature On Governance Committeesmentioning
confidence: 99%